THE EFFECT USING DIFFERENT TYPES OF FORAGE FOR THE MAKING COMPLITE SILAGE TO NUTRIENT CONTENT PRODUCED - Gerson Frans Bira; Paulus Klau Tahuk; Trifobertus Seran (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2020)
The aim of this study was to determine the complete nutrient content of silage made from different types of forage. The study was conducted at the Timor University Faculty of Agriculture, Kefamenanu and the Laboratory of Feed Chemistry Faculty of Animal Science, Nusa Cendana University, Kupang. The research method used was a Completely Randomized Design (CRD) consisting of 3 treatments and 4 replications: T1: 45% Natural grass + 20% Leucaena leucocephala + 25% Corn flour + 10% Bran pollard, T2: 45% Sorghum bicolor (L) Moench + 20% Leucaena leucocephala + 25% corn flour + 10% bran pollard, T3: 45% Pennisetum purpuphoides + 20% Leucaena leucocephala + 25% Corn flour + 10% Bran pollard. The data obtained were processed using variance acording to the Completely Randomized Design (CRD) and Duncan’s test. The results of the study showed that the use of different types of forage had a significant effect (P<0.05) on the complete nutrient content of silage. It was concluded that complete silage with sorghum (T2) forage was significantly higher in producing nutrient content than natural grass (T1) and Pennisetum purpuphoides (T3) that is Dry Matter (DM) of 94.89%, Organic Matter (OM) 88.14%, Crude Protein (CP) 13, 81%, Ether Extract (EE) 7.29%, Crude Fiber (CF) 14,86%, Nitrogen Free Extract (NFE) 52.16% with gross energy and Energy Metabolis (EM) of 17.43 Mj/kg DM, 4151.66 Kcal/Kg DM and 3382.52 Kcal/Kg DM.